PERSEPSI NILAI DAN KUALITAS LAYANAN TERHADAP PERILAKU KEWARGANEGARAAN PELANGGAN APLIKASI GO-JEK - Trevisia Meinar; Tatik Suryani (Faculty of Economic and Business, University of Pasundan, 2019)
This study aims to determine the effect of perceived value and perceived service quality by Go-Jek application users in Surabaya. The population in this study were all Go-Jek users throughout Indonesia. Samples were taken using a non-probability sampling method that specifically uses a purposive sampling technique. Based on the sampling technique, 200 samples were used in this study using Go-Jek in Surabaya. Data collection was carried out using a questionnaire that was distributed directly to respondents. The statistical method used as data analysis is PLS followed by WarpPLS 6.0. The results showed that customer satisfaction partially influenced mediation in service quality with customer citizenship behavior. In addition, customer satisfaction has a partial mediating effect on the perceived value by customer citizenship behavior